Teaching-learning process in mathematics: Scope and importance of previous knowledge - Gabriel Alcívar Zambrano, Juan; María San Andrés Laz, Esthela; Rodríguez Gámez, María (International Journal of Psychosocial Rehabilitation, 2020)
Learning constitutes a weapon provided by nature, from our birth to use it during the course of life in the development of the human species, this process is nourished with knowledge of daily work; the more knowledge is incorporated, the better the students’ rational development will be. Currently there are difficulties with teachers, who do not give the required importance to the previous knowledge that students must have in the subject of mathematics, so the objective of the work is to investigate the teaching-learning process in mathematics, appreciating its scope and importance from previous knowledge in Higher Basic Education and Baccalaureate. In the present investigation, descriptive observation was used, the inductive deductive method to characterize the teaching-learning process, in addition, the quantitative-qualitative was used to evaluate the survey, which was applied to a population of 50 teachers who teach exact science, analysis-synthesis and historical-logic were also used. It was obtained as a result that the teachers are not busy, nor worried about the knowledge of the subject with which their students arrive; then most of them found the transmission of knowledge to the students of exact science complex.